Correlation of serum androgen and gonadotropin with anti-mullerian hormone in polycystic ovarian syndrome in Eastern Indian population - Raghuvanshi, Somnath Singh; Sinha, Anirban; Maiti, Animesh; Chakraborty, Partha Pratim; Basu, Asish Kumar; Ghosh, Sayan; Agrawal, Saurav Shishir; Agrawal, Chhavi (International Journal of Research in Medical Sciences, 2019)
Background: Ovarian steroidogenesis requires gonadotropin stimulation, Luteinizing Hormone (LH) is a key factor in the hyperandrogenaemia of the polycystic ovary syndrome. Progesterone is the primary regulator of Gonadotropin-Releasing Hormone (GnRH) pulse frequency; however, in the polycystic ovary syndrome, the GnRH pulse generator is relatively resistant to the negative feedback effects of progesterone. Study aims to evaluate the association of Anti-mullerian hormone with serum androgen and gonadotropin level in adolescents and young women of Polycystic Ovary Syndrome (PCOS). Methods: This was a single centre observational Cross-sectional study carried out in the department of Endocrinology and metabolism, Medical College, Kolkata from March 2017 to January 2019. Total number of study subjects were 207 out of which 138 were cases. Results: The AMH had strong positive correlation with serum testosterone in both case and control groups (r 0.542, p<0.001 and r 0.57, p<0.001) respectively .After the adjustment of age and BMI , the AMH moderately positive but extremely significant correlation with serum testosterone as compare to control. Conclusions: Hyperandrogenaemia and higher ratio of LH and FSH associated with higher serum AMH level is associated with the higher serum AMH in polycystic ovarian syndrome.